Gender, Writing, and Performance : Men Defending Women in Late Medieval France (1440-1538). - Swift, Helen J. (Oxford modern languages and literature monographs., 2008)
Helen Swift examines late-medieval and early-modern French imaginative literature written by men in defence of women of great popularity in its own time - including catalogues of virtuous women, allegorical narratives, and debate poems. - ;This book explores the poetics of literary defences of women written by men in late-medieval and early-modern France. It fills an important lacuna in studies of this polemic in imaginative literature by bridging the gap between Christine de Pizan and a later generation of women writers and male, Neo-Platonist writers who have recently all received due critic.